2022
DOI: 10.1177/1179173x221137218
|View full text |Cite
|
Sign up to set email alerts
|

Global Status of Knowledge, Attitude and Practice on Tobacco Cessation Interventions Among Dental Professionals: A Systematic Review

Abstract: BACKGROUND With the emergence of the WHO Framework Convention on Tobacco Control, globally the use of tobacco has decreased notably, although, it still requires efforts at individual, organizational, community level to decrease the rate further. Dental professionals are at an excellent position to provide tobacco cessation counselling and interventions, however, it is not practiced much due to lack of training and lack of knowledge. Therefore, this systematic review was conducted to assess the global status of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In this study of participants who self-identified as currently using tobacco and having had a dental visit within the previous year, overall 22.1% reported having had an OOPC screening by a dental professional within the previous year. Overall, there were 41.1% who reported having had a conversation with a dental professional within the previous year about the benefits of tobacco cessation.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In this study of participants who self-identified as currently using tobacco and having had a dental visit within the previous year, overall 22.1% reported having had an OOPC screening by a dental professional within the previous year. Overall, there were 41.1% who reported having had a conversation with a dental professional within the previous year about the benefits of tobacco cessation.…”
Section: Discussionmentioning
confidence: 85%
“…In another systematic review, the authors indicated that there was only low‐certainty evidence of the effectiveness of behavioural support for tobacco cessation, while there was moderate support of a combined behaviour/pharmacotherapy approach 21 . Dental professionals without pharmacotherapy education for tobacco cessation may use such evidence to justify not including tobacco cessation discussions, particularly if there is concern of alienating patients as 25%–50% globally believed inquiring about tobacco use would have a negative influence on their practice 22 . In terms of current global research on tobacco cessation discussions provided by dental professionals, authors of a systematic search indicated that although the studies showed a favourable attitude to tobacco cessation discussions, knowledge was more theoretical than practical: knowledge of the 5As of tobacco cessation was >80%, but practice of using the 5A's (Ask, Advise, Assess, Assist, Arrange) was as low as 11%; knowledge of pharmacotherapy was <75%, but only ten of the studies reported dental professionals prescribing pharmacotherapeutics 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 49 , 50 ] Studies have indicated that currently, the knowledge among healthcare providers is more theoretical than what is being practiced. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%